Pengendalian Persediaan Bahan Baku Keripik Pisang Dengan Metode Economic Order Quantity (EOQ) Pada Umkm Keripik Pisang Muli Zahwa Sungai Langka: Studi kasus pada UMKM Keripik Pisang Muli Zahwa Sungai Langka - nandita ayuni safitri, nandita; Zaini, Muhammad; Noer, Irmayani; Handayani, Sri (Program Studi Pengelolaan Agribisnis, 2025)
This research aims to analyze how to manage raw material supplies at the Muli Zahwa Banana Chips Micro, Small and Medium Enterprises (MSMEs) located in Sungai Langka Village, Pesawaran Regency. These MSMEs are facing several problems, including delays in sending raw materials, limited number of suppliers, as well as immature muli banana raw materials, so that the daily production target of 200 kg cannot be achieved. In February 2025, actual production only reached 2,040 kg from the target of 5,200 kg, or around 38%. The potential production of muli bananas in Sungai Langka Village reaches 133,700 kg per month, while the needs of Zahwa MSMEs are only around 18,200 kg per month. In this research, the Economic Order Quantity (EOQ) method is used to determine the most optimal order quantity for raw materials. The calculation results show that the optimal order quantity is 1.699 kg per order with an order frequency of 14 times per year or 1 times a month. Safety stock is set at 76 kg and the reorder point is 576 kg. By implementing the EOQ method, it is hoped that it can increase operational efficiency, reduce total inventory costs, prevent shortages of raw materials, and improve the smoothness of the production process. This method provides an inventory management approach that is more organized and appropriate to the production capacity of MSMEs, while reducing the risk of wasting raw materials. It is hoped that the results of this research can be a reference for other MSMEs facing the same problems.